AXIOLOGIE - CADRU DE REFERINŢĂ ÎN FORMAREA ORIENTĂRILOR VALORICE LA STUDENŢI - Zoia GUŢU; Maia DOHOTARU (Moldova State University, 2018)
Analizei este supusă problema valorilor și formării orientărilor valorice la studenți din diferite perspective: filosofică, psihologică, sociologică, pedagogică. Accentul se pune pe analiza diferitelor clasificări ale valorilor, pe caracterizarea fenomenului de orientări valorice, acceptând latura educațională a acestora. Totodată, sunt analizate pe larg funcțiile orientărilor valorice: expresivă, adaptivă, protejare, cunoaștere, coordonare. AXIOLOGY - REFERENCE FRAMEWORK FOR TRENING VALUABLE GUIDELINES FOR STUDENTS This article analyzes the issue of values and the formation of value orientations for students from different perspectives: philosophical, psychological, sociological, pedagogical. The emphasis is on the analysis of different classifications of values, on the characterization of the value orientation phenomenon, accepting their educational side. At the same time, the functions of the value orientations are expressed extensively: expressive, adaptive, protection, knowledge, coordination.